The effect of some factors on expression of gene encoding endoglucanase from dna metagenome of Binh Chau hot spring in Escherichia coli - Thuy, Tran Thanh; Nhung, Lai Thi Hong; Man, Tran Dinh; Xuan, Le Thi Thanh; Thoa, Nguyen Kim (Academia Journal of Biology, 2019)
Expression of microbial target genes in Escherichia coli is broadly used due to its advantages namely: well established system, easy to manipulate, a huge biomass, high level productivity, safe and inexpensive to grow. Metagenomic technique has been applying in Vietnam recently for effective mining of uncultured gene resources, especially in endemic mini-ecologies such as hot springs where the cell densities are low. DNA metagenome of Binh Chau hot spring was isolated and sequenced by Illumia HiseqTM. Based on analyses of databases of cellulase-encoded genes, denovogenes 18736 gene sequence for thermal endoglucanase was selected for expression in E. coli. In this paper, some factors for expression of endoglucanase have been investigated. The results show that appropriate gene expression conditions are:  Expression performed in E. coli C43 (DE3) on TB medium at 30oC with 0.25 mM of IPTG as inducer, the culture volume of 20% compared with the bottle volume and the expression time is 42–48 hours. In this condition, the biomass production and soluble enzyme activity can reached up to 5.54–5.58 g /L and  1.92–1.98 U/mL, respectively. Our results show the prospect of exploiting microbial genes without culture.